Subdivision of the Nazca Plate into three new tectonic plates and it’s incident with the peruvian current seismicity - Vela Velásquez, Churchill (2009)
The Andean Cordillera was formed at the forefront of the South American Plate as a consequence of the collision of this Plate with the Nazca Plate. The Cordillera was later progressively deformed by subsequent tectonic events. The associated stresses acted on the volume of lithosphere between the Peru-Chile Trench on the west, and, the Brazilian Shield on the east. The base of the lithosphere at the root of the Andes takes the form of a surface concave upwards, a consequence of the tectonics and the weight of the lithosphere. This root sinks into the fluids of the Upper Mantle favoring a lithosphere thickness of 200 Km, plus the 7 Km elevation above sea level of the Central Andes. The new tectonic model herein proposed considers the division of the Nazca Plate into three segments: 1) Southern Nazca Plate, 2) Central Nazca Plate, 3) Northern Nazca Plate. Furthermore, it is proposed that the Cocos Plate be considered a Sub-Plate which, based on similar deformational mechanisms with the Galapagos Sub-Plate should together constitute the Nazca Plate North. Evidence is presented that there are seismic cycles with recurrence periods of 33 to 40 years. The Central Northern Block is under the seismic cycle “1985-2019” and a return is expected of the seismic cycles of “1914-1950” and “1951-1984”. Catastrophic events associated with these cycles include in 1940 in Lima, 1944-1946 in Libertad and Ancash, 1970 in Huaraz, 1974 in Lima, and 1976 in North Coast. Evidence will be shown that supports the hypothesis that past seismic events in Peru are related to faulted blocks on the western edge of the South American Plate. Two important expressions of this relationship are the Paracas Fault and the Gulf of Guayaquil Fault. The former one was formed by recent tectonic events and related to hypocenters during seismic movements in 1908, 1946 and, the most recent earthquake in Pisco on August 15, 2007 with hypocenter at 39 km below ground surface.